Принципы и модели энергосберегающего автоматизированного управления режимами работы конденсаторов паровых турбин тепловых и атомных электростанций - Канюк, Г. И.; Мисько, А. Р.; Лаптинов, И. П.; Стеблянко, Д. Д. (НТУ "ХПИ", 2011)
The task of creation of the energysaving system of automatic control the modes of operations of condensers of steam-turbines is formulated. The general mathematical model of the stationary mode of operations of condenser is developed. The algorithm of the standard program of functioning of condenser is formed at the set values of charges of steam and runback.
Keywords: экономичность электростанций; низкопотенцимальные комплексы; конденсационные установки